Smart E-Learning Systems for Japanese Literature Education in an Industry 4.0 Perspective - Unsriana, Linda; Perdana, Bosya; Ariana, Sunda; Saputra, Dhimas Rosanto (Aptisi Transactions On Technopreneurship (ATT), 2026)
The Industrial Revolution 4.0 has reshaped educational practices, prompting the integration of e-learning to overcome conventional pedagogical constraints in specialized fields like Japanese literary studies. This study investigates the efficacy, challenges, and optimization strategies of technology-enhanced learning for Japanese literature. Utilizing a qualitative case study approach, data were collected via interviews with instructors and students, observations of LMS, and analysis of digital resources across universities adopting e-learning for Japanese literature. Thematic evaluation and Kirkpatrick’s model revealed that e-learning improves student engagement through digital forums and multimedia tools, facilitating deeper cultural and contextual understanding of literary texts. However, technical barriers (e.g., inconsistent internet access, infrastructure gaps) and pedagogical challenges in conveying the aesthetic essence of literature digitally remain significant hurdles. To address these, the study advocates for AI-powered text analysis tools, gamification, and adaptive learning systems to enhance interactivity and motivation. Findings emphasize e-learning’s potential to transform Japanese literary education when supported by tailored digital frameworks. Recommendations include institutional investments in infrastructure, educator training, and further research on adaptive technologies. This work bridges digital pedagogy and literary studies, offering insights to align humanities education with Industry 4.0 demands while preserving academic rigor in a technology-driven era.